The Act of Seeing with Mechanical Eyes - Anderson, Steve F. (Imaginations, 2026)
This article expands upon and documents a practice-based inquiry into the transformation of contemporary visual culture, engaging debates around machine vision, operational imaging, and generative AI. Featuring a series of original digital artworks alongside the multimodal interactive/immersive environment Machine Visions: Mojave, the article situates hybrid images and environments as neither purely representational nor rigidly instrumental, but as sites where perception, computation, and environmental awareness are actively co-produced. The Mojave Desert—where Joshua trees serve as a climate-sensitive bioindicator—functions as both object of study and critical test case, revealing the speculative potentials of more than human ways of seeing and knowing.